Pengaruh Alat Permainan Edukatif (APE) Monopoli Terhadap Pemahaman Anak Usia Dini Tentang Uang Dan Pengelolaan Keuangan - Resiana, Rani Surya; Pratiwi, Siti Nur Elbayyinah Rahayu (LP2M STAI Al-Musaddadiyah Garut, 2024)
This research aims to describe young children's understanding of money and financial management using the monopoly educational game tool.This research is experimental research and involves two variables, namely the independent variable and the dependent variable, the independent variable is the monopoly educational game tool and the dependent variable is young children's understanding of money and financial management. The population in this study were all Kober Kurnia and RA Nabila Azzahra Wanaraja. students with a total of 130 students. Sampling was carried out by purposive sampling, the sample in this study was 99 students. The instrument used is a test of children's understanding of money and financial management. The results of data analysis show that the average score of children's understanding of money and financial management in the experimental class is 66.81% and the average score of children's understanding of money and financial management in the control class is 32.7%. The results of the hypothesis test used the t test, where the calculation results obtained tcount > ttable, namely 4.829 > 1.677. From the results of this analysis, it was found that there were differences in children's understanding of money and financial management between students who learned through the monopoly game and students who did not learn through the monopoly game. Likewise, the results of children's understanding of money and financial management using the monopoly game are higher than those of students who do not learn using the monopoly game. Keywords: Monopoly educational game tools, money and financial management, early childhood